ON TWO POSTLARVAL STAGES OF THE SHAD HILSA KELEE (CUVIER) - Bensam, P (Indian Journal of Fisheries, 2011)
Two postlarvae of H. kelee measuring 5.68 mm and 7.92 mm, collected from Gulf of Mannar off Mandapam, are described. In the smaller larva the larval flnfold was prominent and there were 34 preanal and 9 postanal myomeres. In the larger one the flnfoid was almost absent; all the fins except the pelvic had been developed and there were 27 preanal and 16 postanal myomeres. Pigmentation in both the stages was sparse. The differences in features between present postlarvae and similar stages of allied clupeids from Indian region are discussed.